A study on the diversity, marketing and conservation status of different aquatic food fauna in Kokrajhar, Assam, India - Boris Machahary; Barasha Das; Bronson Kumar Khangembam (Journal of Fisheries, 2023)
Kokrajhar district of Assam in North-eastern India has several natural water resources that harness a variety of aquatic fauna. Understanding the aquatic biodiversity is vital for the sustainable development of fisheries and aquaculture expansion. The present study aims to record the diversity and marketing of aquatic food faunal resources in Kokrajhar, Assam. Surveys were conducted in three village markets and two town markets of Kokrajhar. Altogether, 64 finfish, 6 shellfish and 4 aquatic insect species were recorded. The abundant presence of diverse small indigenous fish species indicates the potential for the aquaculture expansion of these species in the region. Majority of the species (77%) were found to be Least Concern, whereas, 5, 3 and 1 species were Near Threatened, Vulnerable and Endangered respectively as per IUCN Redlist database. A higher demand and market price were observed for all locally captured species. This study has highlighted the rich aquatic food faunal biodiversity of Kokrajhar and the socio-economic condition of the local fishers. The information from this study may be useful in the sustainable development of fisheries and aquaculture in the region.